(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Cisplatin (CIS), a known anticancer drug, has side effects initiated by oxidative damage which hinders its use. Raffia hookeri pulp extract (RHPE), reported to possess antioxidant activity should mitigate cisplatin toxicity. The present study examined the potential of RHPE to reduce brain damage in rats exposed to cisplatin. Forty eight female rats (150 g – 220 g) were randomized into four groups (n = 12) viz: Group 1 served as control received distilled water daily, Group 2 received 100 mg/kg body weight of RHPE, Group 3 received CIS (7.5 mg/kg body weight, intraperitoneally) as single dose, Group 4 received 100 mg/kg body weight of CIS+RHPE. The RHPE was given orally via gavage for 14 days while the single dose of cisplatin was administered on the eighth day of experiment. Behavioral tests namely: transitions, rearings, groomings and forelimb grip strength were carried out on 15th day of the experiment after which rats were euthanized followed by histology and histomorphometry. Cisplatin significantly (p<0.05) reduced the percentage body weight changes, transitions, rearings, groomings and forelimb grip strength compared with the control group, whereas treatment with CIS+RHPE significantly (p<0.05) increased these parameters compared with Cisplatin treatment. Cisplatin also caused histological alterations of Purkinje neurons, pyramidal neurons of Cornu ammonis3, granule cells and cerebral cortex neurons. It significantly (p<0.05) reduced the diameter of Purkinje (9.1±0.59 μm) compared with control (14.41±0.31 μm) and pyramidal neurons (11.32±0.05 μm) compared with control (17.03±0.54 μm). Rats in the CIS+RHPE had their histology considerably improved compared with those of cisplatin. In conclusion, RHPE reversed the behavioural changes and demonstrated neuroprotection against CIS-induced behavioural changes and microanatomical alterations of cerebellar, hippocampal and cerebral neurons